2023
DOI: 10.1212/wnl.0000000000201367
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obesity With Cognitive Decline in Black and White Americans

Abstract: Background and Objectives:There are disparities in the prevalence of obesity by race and the relationship between obesity and cognitive decline is unclear. The objective of this study was to determine whether obesity is independently associated with cognitive decline and if the association between obesity and cognitive decline differs in Black and White adults. We hypothesized that obesity is associated with greater cognitive decline compared to normal weight, and that the impact of obesity on cognitive declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Additionally, research has shown a connection between obesity in early old age and a decrease in cortical thickness [66]. These findings collectively suggest that obesity and its associated metabolic problems may contribute to increased microvascular brain damage and neuroinflammatory events, ultimately leading to cognitive decline [62].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, research has shown a connection between obesity in early old age and a decrease in cortical thickness [66]. These findings collectively suggest that obesity and its associated metabolic problems may contribute to increased microvascular brain damage and neuroinflammatory events, ultimately leading to cognitive decline [62].…”
Section: Discussionmentioning
confidence: 98%
“…Regrettably, the brain is not exempt from these inflammatory effects, which can ultimately accelerate the progression of cognitive decline and increase the risk of developing AD [60]. Obesity may be associated with higher levels of proinflammatory cytokines (like interleukin-1β) in the brain [61], which may explain why obesity remains linked to executive function even after accounting for blood pressure (BP) and fasting plasma glucose (FPG) [62]. Neuroinflammation related to obesity and activation of microglia induces synaptic remodeling and neuronal apoptosis and decreases neurogenesis, which has been associated with cognitive decline [63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, physical activity participation is linked to lower AD/ADRD risk, but physical activity likewise helps in mitigating obesity and preserving muscle strength [ 29 ], and may have implications for cognitive function earlier in life [ 30 ]. Moreover, physical activity combats obesity [ 31 ], which in turn, is linked to executive function and dementia [ 32 ]. As such, physical activity could be particularly important for the triangulation between strength capacity, obesity status, and cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in cognitive function can be potentiated since middle-aged adults with obesity may experience differentially greater brain atrophy [ 37 ]. The relationship between a higher BMI and reduced cognitive performance does not change with age [ 45 ] or race [ 46 ]. A high intake of fat and sugar is associated with impairments in hippocampal-dependent learning and memory in children [ 47 ] and adults [ 48 , 49 ], suggesting a negative impact on hippocampal function across the lifespan.…”
Section: Obesity Induces Cognitive Declinementioning
confidence: 99%